2014
DOI: 10.1021/jf405504u
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Antihyperuricemic Peptides in the Proteolytic Digest of Shark Cartilage Water Extract Using in Vivo Activity-Guided Fractionation

Abstract: A peptide that exerts antihyperuricemic activity after oral administration was identified from a microbial protease (alcalase) digest of the water extract of shark cartilage by in vivo activity-guided fractionation, using oxonate-induced hyperuricemic rats. Water extract of shark cartilage was first fractionated by preparative ampholine-free isoelectric focusing, followed by preparative reversed-phase liquid chromatography. The antihyperuricemic activity of the alcalse digests of the obtained fractions was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 16 publications
2
60
0
Order By: Relevance
“…The type of bioactive peptides generated from a particular protein is dependent on the primary sequence of the protein and the specificity of proteases used to generate peptides [ 3 , 20 ]. Proteins and peptides from cartilages of Chondrichthyes have been investigated as a good source for searching antiangiogenesis, antioxidant, and antihyperuricemic agents [ 21 , 22 , 23 ]. Therefore, in the experiment, crude proteins of spotless smoothhound cartilage were extracted using HCl-Guanidine buffer with yield of 1.69% ± 0.03% (on dry cartilage), and hydrolyzed for 4 h using trypsin at pH 8.0, 40 °C with a total enzyme dose of 2.5%.…”
Section: Resultsmentioning
confidence: 99%
“…The type of bioactive peptides generated from a particular protein is dependent on the primary sequence of the protein and the specificity of proteases used to generate peptides [ 3 , 20 ]. Proteins and peptides from cartilages of Chondrichthyes have been investigated as a good source for searching antiangiogenesis, antioxidant, and antihyperuricemic agents [ 21 , 22 , 23 ]. Therefore, in the experiment, crude proteins of spotless smoothhound cartilage were extracted using HCl-Guanidine buffer with yield of 1.69% ± 0.03% (on dry cartilage), and hydrolyzed for 4 h using trypsin at pH 8.0, 40 °C with a total enzyme dose of 2.5%.…”
Section: Resultsmentioning
confidence: 99%
“…The XO inhibition assay was carried out following the method of Murota et al . () with slight modifications. Fifty microlitre xanthine (6 mmol L −1 ), 50 μL XO (15 mU mL −1 ), 200 μL TPH, TPH‐M or TPH‐D were mixed in the wells of a 96‐well plate, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Murota et al . () found that Ser‐Pro‐Pro‐Tyr‐Trp‐Pro‐Tyr exhibited significantly different antihyperuricemic activity after oral administration or intravenous injection. In addition, during food processing and storage, Maillard reaction occurs spontaneously mainly through the interaction between reducing sugars and amino groups.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Obviously, non-specific proteases will release far more peptides. The traditional strategies involve assay-guided consecutive separation, including membrane filtration, isoelectric focusing, gel filtration, ion exchange and reverse phase chromatography, which need the analysis of activities fraction by fraction [ 18 , 19 , 20 , 21 ]_ENREF_14. Although these procedures are feasible, they are time-consuming and labor-intensive and give rise to problems such as poor isolation yields and loss of biological activity during operation.…”
Section: Introductionmentioning
confidence: 99%